Component procurement and end product assembly in an uncertain supply and demand environment - Bollapragada, Ramesh; Kuppusamy, Saravanan; Rao, Uday S. (International journal of production research, 2015)
In this paper, we examine a multi-product, multi-component, procurement and assembly problem with both supply and demand uncertainties. We explicitly model the uncertainty using a stochastic program that facilitates procurement and assembly decisions. We present a stochastic linear programming model of the problem which we solve using its deterministic equivalent with a finite number of scenarios. We show that the systems performance, i.e. total cost, depends on the order lead time, L, and the assembly lead time Q, only through their sum . We illustrate the impact of on system performance with numerical experiments. Also, we illustrate that, in some cases, increasing supplier capacity can worsen system performance. In addition, we identify the key cost drivers that need attention from managers in the manufacturing industry, when there is limited knowledge of future demand and component availability.